A SCOPING REVIEW: THE IMPACT OF PORNOGRAPHY ADDICTION ON ADOLESCENTS - Sarfi Agustina Tri Astuti; Yuliani Winarti (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
The current digitalization process is overgrowing so that internet access becomes more effortless. This has led to an increase in youth exposure to pornography. Prolonged exposure to pornography can negatively impact adolescent development and lead to addiction. This study aims to map the impact of pornography addiction on adolescents using Preferred Reporting Items for Systematic Reviews and Meta-Analyze Extensions for Scoping Reviews through Pubmed, Google Scholar, Scopus, and Science Direct. The results showed that 14 of the 3,124 research articles that met the inclusion criteria stated that there were 3 effects of pornography addiction: psychological, social, and medical. The psychological impact of excessive consumption of pornography can be in the form of irritability, difficulty concentrating, stress, guilt, frustration, feelings of depression, difficulty sleeping, and psychosomatic symptoms. While the social impact that occurs in pornography addicts is difficulty establishing interpersonal relationships with other people, tend to withdraw, prefer to remain silent, and feel distant from society. As for the medical impact that occurs, based on the results of brain wave recording through electroencephalography (EEG) examination, there is a dominance of delta waves in the prefrontal cortex, which causes a decrease in cognitive function of adolescent porn addicts. This causes adolescents to lose the ability to determine what is right and wrong or refrain from doing wrong. Based on the results of this study, health promotion efforts need to be carried out, one of which is education about the impact of pornography addiction in improving the health status of adolescents.